2021
DOI: 10.3389/fmicb.2021.642730
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Root-Associated Bacteria and Fungi of Astragalus mongholicus and Their Relationship With the Bioactive Ingredients

Abstract: Astragalus membranaceus (Fisch.) Bge. var. mongholicus, which is used in traditional Chinese medicine, contains several bioactive ingredients. The root-associated microbial communities play a crucial role in the production of secondary metabolites in plants. However, the correlation of root-associated bacteria and fungi with the bioactive ingredients production in A. mongholicus has not been elucidated. This study aimed to examine the changes in soil properties, root bioactive ingredients, and microbial commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…Previous studies found that some endophytic bacteria of Macleaya cordata and Astragalus mongholicus showed significant correlation with the contents of alkaloids [47,48]. They inferred that difference in the contents of alkaloids by the host or host compartments may contribute to difference in the endophytic bacterial community structure [47,48]. In this study, RDA and Pearson correlation analysis uncovered that five endophytic bacterial genera showed significant correlation with four alkaloids contents of A. carmichaelii Debx.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies found that some endophytic bacteria of Macleaya cordata and Astragalus mongholicus showed significant correlation with the contents of alkaloids [47,48]. They inferred that difference in the contents of alkaloids by the host or host compartments may contribute to difference in the endophytic bacterial community structure [47,48]. In this study, RDA and Pearson correlation analysis uncovered that five endophytic bacterial genera showed significant correlation with four alkaloids contents of A. carmichaelii Debx.…”
Section: Discussionsupporting
confidence: 52%
“…Some endophytes can produce or transfer host plants' secondary metabolites [3] and host plant metabolites can shape the root microbiota [14,15]. Previous studies found that some endophytic bacteria of Macleaya cordata and Astragalus mongholicus showed significant correlation with the contents of alkaloids [47,48]. They inferred that difference in the contents of alkaloids by the host or host compartments may contribute to difference in the endophytic bacterial community structure [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Glomus intraradices altered the relative quantity of essential oil patterns and significantly increased bornyl acetate, 1,8-cineole, α- and β-thujones in Salvia officinalis [ 242 ]. Li et al [ 256 ] found that bacterial and fungal community composition around the rhizosphere varied over the cultivation years of Astragalus mongholicus . The richness of Stenotrophomonas was positively correlated with astragaloside content, while Phyllobacterium and Inquilinus were positively correlated with calycosin content in roots.…”
Section: Function Of Soil Microorganisms In Growth Promotion and Qual...mentioning
confidence: 99%
“…In recent years, more and more studies have focussed on the correlation between PGPR and active ingredients of medicinal plants. Root‐associated bacteria and fungi played a crucial role in the production of secondary metabolites, such as astragaloside and calycosin by Astragalus membranaceus (Li et al, 2021). The application of arbuscular mycorrhiza fungi and PGPR played a significant role in increasing yields, bioactive compounds and nutrition in the medicinal plant Basil (Khalediyan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%